Students' Engagement in the Implementation of Flipped Classroom for English Lessons - Sunway, Angelia Widia; Arapah, Elvina; Muth'im, Abdul (Journal of English Education Program, 2024)
This study aims to describe the students"™ engagement in the implementation of the flipped classroom method in the English lessons during the post Covid-19 pandemic. This research used a descriptive qualitative design, and the techniques of collecting data were observation and interview. The data were obtained from 23 students as research subjects. Findings of this research show that the students have positive engagement with the implementation of the flipped classroom method in the post-Covid-19 pandemic. Positive student engagement can be seen based on students' attitudes, which show indicators in the three dimensions of student engagement: behavioral, emotional, and cognitive engagement in a positive sense. This has been proven by the student response data which show that the students were enthusiastic about the learning activities conducted in the flipped classroom because they already had the knowledge they gained before the meeting. Students feel more prepared to participate in the discussion process in class, enthusiastically participate in the learning activities, and can study independently.